Effect of MnO2 on the microstructure and electrical properties of 0.83Pb(Zr0.5Ti0.5)O3-0.11Pb(Zn1/3Nb2/3)O3-0.06Pb(Ni1/3Nb2/3)O3 piezoelectric ceramics. Issue 1 (January 2020) - Li, Leilei; Liu, Junting; Xu, Jie; Cao, Shuyao; Chen, Qian; Pawlikowska, Emilia; Szafran, Mikołaj; Gao, Feng; Reece, Mike; Yan, Haixue
Abstract: A sample of 0.83Pb(Zr0.5 Ti0.5 )O3 -0.11Pb(Zn1/3 Nb2/3 )O3 -0.06Pb(Ni1/3 Nb2/3 )O3 (PZNNT) to which MnO2 was added, with a high mechanical quality factor (Qm ) and a good transduction coefficient (d33 ×g33 ), were systematically investigated. Based on the SEM analysis there existed two kinds of "secondary phases", Rich Ti and Rich Zn phases, which arose due to the B-site substation of PZNNT-based ceramics by manganese ions. One phase was due to the Mn 3+ replacing the Ti 4+ to create oxygen vacancies and induce the hardening effect. Another phase was due to the Mn 2+ replacing the Zn-site to stabilize the perovskite phase. When the addition of MnO2 reached the solubility limit of 1.5 mol% in the PZNNT-based ceramics, the sample showed optimal electrical properties (Qm =357, d33 ×g33 =9859 × 10 −15  m 2 /N, kp =0.56), which suggested its potential application for piezoelectric energy harvesting in larger field excitation environments.